2021
DOI: 10.5937/poljteh2101032o
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest processing, packaging and storage of African oil bean seed

Abstract: The underutilization of African oil bean seed necessitated the study of its post-harvest operations. This work reviews the status of research on postharvest processes of African Oil Bean (AOB) seed. Information was sought through a search query with African oil bean post-harvest processing, packaging and storage as keywords on Google Scholar, internet, publishers' website, textbooks and oral interview with local processors. The results showed that researchers have focused on the fermentation, proximate, phytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The seeds are flat and brown and are contained in a brown, flattened pod [ 18 , 19 ]. They have an average length of 56 mm and a width of 37 mm [ 5 ]. The number of seeds in each pod depends on the length of the pod and on the size of the seeds within (usually 6 to 10 seeds in each pod).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The seeds are flat and brown and are contained in a brown, flattened pod [ 18 , 19 ]. They have an average length of 56 mm and a width of 37 mm [ 5 ]. The number of seeds in each pod depends on the length of the pod and on the size of the seeds within (usually 6 to 10 seeds in each pod).…”
Section: Methodsmentioning
confidence: 99%
“…It is valued in southeastern Nigeria for its soil improvement properties [ 4 ]. African oil beans (AOB) are edible oil seeds that are rich in protein (22%) and oil (52%) [ 5 ]. AOB is characterised by its bountiful harvest in Nigeria and other African countries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out by Sanni et al (2002) reported that sensory attributes (consistency, taste and aroma) of ugba produced using a starter culture was better than ugba samples obtained from retail markets. Both traditional and improved methods of processing African oil bean seeds into ugba have been described by many researchers (Ogbulie et al, 2014;Okereke and Chuka, 2017;Nwokeleme and Ugwuanyi, 2015;Okorie and Olasupo, 2013;Onyekachi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…predominates other microorganisms involved in the fermentation process of oil bean seeds after 24 hours till the process ends Ogueke et al, 2015). According to Onyekachi et al (2021), ugba is produced as a result of Bacillus pumilus, B. sphaericus, B. licheniformis and B. subtilis involvement in the fermentation of African oil bean seeds. The activities of microorganisms and biochemical changes which occur during fermentation of African oil bean seeds slices influence the organoleptic properties of ugba (Kabuo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%